Guava-Enriched Dairy Products: A Review - Chauhan, Anil Kumar; Singh, Smita; Singh, Ravi Pratap; Singh, S P (Indian Journal of Dairy Science, 2015)
Guava (Psidium gujava) is a worldwide popular tropical fruit with high content of vitamins & phytochemicals. The traditional therapeutic benefits of guava over metabolic disorders, gut infection, diabetes and obesity have been proven, but available processed guava products confront limitation only to biscuits, jams, jellies, marmalades etc. Guava contains immense bioactive potential and good source of dietary fiber which function as prebiotic; its combination with probiotic fermented dairy food like whey protein, yoghurt, curd and shrikhand will develop high value commodities to increase nutrition profile of guava in the area of functional foods. This paper summarizes an extensive exploration for development of guava fortified fermented dairy foods; various dimensions of technological challenges and recent formulation designed for health benefits and consumer preference.